Recombinant serralysin metalloproteases D enhances the intracellular replication of infectious bovine rhinotracheitis virus - Yan, Longfei; Li, Yanran; Qi, Jiancheng; Ren, Li; Zhou, Xueke; Gou, Liping; Zuo, Zhicai (Frontiers in Microbiology, 2025)
Infectious bovine rhinotracheitis virus (IBRV) and Serratia marcescens co-infection are commonly observed in the respiratory tract of cattle subjected to respiratory diseases. However, the potential effects of proteases from Serratia marcescens on the IBRV infection remain poorly understood. In this study, we investigated the role of recombinant serralysin-like protease D (rSPD) in modulating IBRV infection in Madin-Darby bovine kidney (MDBK) cells. Our findings demonstrate that rSPD enhances IBRV replication and exacerbates the cytopathic effects of the virus on MDBK cells. Quantification of IBRV gB gene copy numbers using fluorescence quantification PCR (FQ-PCR) revealed that rSPD promotes viral replication during the intracellular stage, without affecting viral adsorption, entry, or directly interacting with viral particles. The transcriptomic analysis further demonstrated that rSPD suppresses innate immune responses while amplifying inflammatory pathways in IBRV-infected MDBK cells. Gene Ontology (GO) and KEGG enrichment analysis identified significant enrichment of differentially expressed genes (DEGs) in key signaling pathways, including JAK–STAT, NOD-like receptor, Toll-like receptor, TNF, NF-κB, and MAPK pathways. Notably, rSPD downregulated genes associated with innate immunity, such as ISG15, OAS2, IFIT1, IFIT2, IFIT3, MX1, RSAD2, MX2, SAA3, DDX58, IFI44, and IRF1, suggesting that rSPD suppresses host antiviral defenses. Conversely, rSPD upregulated genes involved in inflammatory response, including IL-6, IL-8, CCL2, CX3CL1, CCL3, and CXCL3, indicating that rSPD may exacerbate cellular damage and promote viral replication by inducing excessive inflammatory responses. These findings provide novel insights into the interplay between bacterial proteases and viral infections, highlighting the potential role of bacterial proteases in exacerbating viral pathogenesis and offering a foundation for further research into therapeutic strategies targeting bacterial-viral interactions.